2007
DOI: 10.1111/j.1360-0443.2007.01874.x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and cardiovascular pathology: a review of the evidence

Abstract: There is sufficient clinical and experimental evidence to suggest that methamphetamine can have adverse and potentially fatal effects on the cardiovascular system. The existing literature suggests that: (1) methamphetamine users are at elevated risk of cardiac pathology; (2) risk is not likely to be limited to the duration of their methamphetamine use, because of the chronic pathology associated with methamphetamine use; (3) the risk of cardiac pathology is greatest among chronic methamphetamine users; (4) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(197 citation statements)
references
References 67 publications
5
191
0
1
Order By: Relevance
“…14,17 In the current study, 10 patients (4.3%) died after being admitted to the ICU, presumably due to drug-related toxicity. Knudsen et al reported an amphetamine-related mortality rate of 12.3% among γ-hydroxybutyrate poisoning cases in Sweden.…”
Section: Discussionmentioning
confidence: 59%
“…14,17 In the current study, 10 patients (4.3%) died after being admitted to the ICU, presumably due to drug-related toxicity. Knudsen et al reported an amphetamine-related mortality rate of 12.3% among γ-hydroxybutyrate poisoning cases in Sweden.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, in respect to increase in frequency of METH use, cardiotoxicity of METH can be considered as a medical concern that needs to effective treatment. The main proposed mechanisms for METH cardiotoxicity is the induction of sympathomimetic effects on central and peripheral nervous system which leads to elevation of circulating catecholamine concentration (4)(5)(6)(7). In fact, high concentration of catecholamine causes narrowing and spasm of the blood vessels, tachycardia, hypertension and probably, death of the cardiomyocyte (8) .…”
Section: Introductionmentioning
confidence: 99%
“…It releases the neurotransmitters dopamine, norepinephrine and serotonin and activates the cardiovascular and central nervous systems, and is highly addictive [4]. It triggers vasospasm, causing persistent tachycardia, hypertension, and/ or direct myocardial toxicity [5,6]. Moderate doses of MA can increase cardiac output and myocardial contractility, but larger doses can cause depression of the myocardium.…”
Section: Discussionmentioning
confidence: 99%